Languages Disenfranchisement in the European Union - Shlomo Weber; Victor Ginsburgh (Fondazione Eni Enrico Mattei (FEEM), 2004)
We introduce the notion of language disenfranchisement which arises if the number of EU working languages is reduced. We use the data on language proficiency in EU and show that, in spite of the widespread knowledge of English, the retention of French and German as working languages in essential to avoid a too large degree of disenfranchisement of citizens. The picture, however, becomes somewhat different if we consider the population under age of 40. We also argue that even though French is the second leading language within the EU, the situation is likely to be reversed after the enlargement.
Keywords: D70; O52; Z13; 330; Languages; Disenfranchisement; European Union; Mehrsprachigkeit; Sprache; Partizipation; EU-Staaten; Fremdsprache